Genetic algorithm active vibration control of a flexible plate structures - Mat Darus, Intan Zaurah (2007)
This paper presents the development of an active vibration control (AVC) mechanism for a flexible plate structure using a Genetic Algorithm (GAs) strategy. The global optimisation technique of GAs is utilised to obtain a dynamic model of a flexible plate structure and verified within the AVC system. The GA based AVC algorithm thus developed is implemented within a flexible plate simulation environment and its performance in the reduction of vibration of the plate is assessed. The validation of the algorithm is presented in both the time and frequency domains. An assessment of the results thus obtained is given in comparison to the AVC system using conventional recursive least squares (RLS) method. Investigations reveal that the developed GA based AVC system performs better in the suppression of vibration of a flexible plate structure compared to an RLS based AVC system.